Environmental Assessment and Sustainable Development in the United States - Toshiyuki Sueyoshi; Youngbok Ryu (Energies, 2021)
This study aims to overview the U.S. sustainable development by measuring the environmental performance of 50 states over the period of 2009–2018. To attain the objective, we employ data envelopment analysis for environmental assessment where we prioritize the minimization of CO2 emissions first and the maximization of gross state product later under the concept of managerial disposability (i.e., an environment-based performance measure). Then, we examine how the state-level environmental performance measures are associated with their political and spatial contexts. For the purpose, we conduct the Kruskal-Wallis rank sum test across groups of states characterized by their political transitions in the presidential and gubernatorial elections and defined by the regions of the U.S. Economic Development Administration and Environmental Protection Agency. Based on our empirical results, we find that (a) overall environmental performance has gradually enhanced over time, (b) there are statistically significant differences in the environmental performance measures along with the political transitions, and (c) states on both coasts have outperformed those of the middle in the measurement.